Speech Function in Bilingual Setting: Associating Learners’ Standpoint - Husnul Khatimah (Journal La Edusci, 2022)
The goal of this research is to investigate students' impressions of the speech function used in a bilingual classroom. The descriptive qualitative method was chosen as the research strategy in this study. The pupils' impressions of speech function were documented by the observation technique. This comprises field notes, interviewing subjects, and taking notes. Transcription, categorization, and conclusion are all phases in data analysis. The outcomes of this research indicate that students have a favorable opinion of the speech functions utilized in the bilingual class system at Muhammadiyah University of Makassar's department of social politics. And that the employment of poetic and phatic functions in the classroom has an influence on the students' capacity to communicate successfully.